The effects of adenosine triphosphate and adenosine diphosphate on transmission at the rat and frog neuromuscular junctions - Ribeiro, J.A. (1975)
1 The effects of adenosine triphosphate (ATP) and adenosine diphosphate (ADP) were investigated on evoked end-plate potentials (e.p.ps) and on miniature end-plate potentials (min. e.p.ps) recorded from muscle fibres of the rat diaphragm and the frog sartorius. 2 ATP and ADP decreased the quantum content of the e.p.ps and the frequency of the min. e.p.ps. The maximum effects produced by the two substances were similar. 3 The potency of ATP was found to be similar to that of adenosine. In the presence of adenosine, in a concentration producing its maximum effect, the addition of ATP had no further effect. This is compatible with the idea that ATP acts in the same way as adenosine.